Surface acoustic waves and devices - B. A. AULD (Archives of Acoustics)
The purpose of this paper is to review the basic physics of surface wave propagation on piezoelectric substrates, and to survey the applications of these waves to various types of devices. Smooth, layered, and corrugated substrates will be considered. Methods of analysis will be reviewed, and general characteristics of the solutions (polarization, velocity, piezoelectric coupling, etc.) will be summarized. To conclude, a brief overview of the historical development of surface wave devices (delay lines, resonators, correlators, convolvers etc.) will be presented, and recent trends in applications will be described.